Two-dimensional electrophoresis protein profiles of HL-60 and CCRF-CEM cell lines treated with epigenetic modification drugs - Sudin, Aziee; Mohd Yassim, Haiyuni; Mohamed Yusof, Shafini; Shamsuddin, Shaharum; Abdul Wahab, Ridhwan; Johan, Muhammad Farid (Malaysian Society For Molecular Biology & Biotechnology, 2019)
Leukemia is classified as a malignant disease of hematopoietic stem cells (HSCs) that fails in cell differentiation but preserve their self-renewal. It is caused by genetic alterations and epigenetic modifications resulting in the activation or inactivation of particular genes for transcription. Epigenetic causes changes in gene expression without any alteration in the DNA sequence. The most common epigenetic modifications are DNA methylation and histone acetylation. 5-Azacitidine (5-Aza) is a DNA methytransferase inhibitor (DNMTi) that inhibits DNA methyltransferase enzymes resulting in hypomethylation. Trichostatin A (TSA) is a histone deacetylase inhibitor which inhibits deacetylation of both histone and non-histone proteins resulting in chromatin relaxation. This present study focused on the alteration of proteome profile on 2D gel electrophoresis (2-DE) induced by 5-Aza and TSA in HL-60 and CCRF-CEM cell lines as in vitro model to represent acute promyelocytic leukemia (APL) and T-lymphoblastic leukemia (T-ALL), respectively. Total proteins of untreated and 5-Aza/TSA-treated HL-60 and CCRF-CEM cell lines were extracted using urea/thiourea buffer and stained with Coomassie Blue. Comparative analysis of untreated and 5-Aza/TSA-treated HL-60 and CCRF-CEM was performed by PDQuest software. Qualitative analysis identified 190-659 protein spots detected in untreated, 5-Aza and TSA-treated HL-60 and CCRF-CEM. Quantitative comparison analysis was analyzed by over 2-fold change in 5-Aza/TSA-treated cells compared to untreated. One and eight upregulated proteins were detected in 5-Aza and TSA-treated HL-60, respectively. While five and one upregulated proteins were detected in 5-Aza and TSA-treated CCRF-CEM, respectively. These preliminary results suggested that 5-Aza and TSA induced proteome profiles alterations due to their inhibition effects in HL-60 and CCRF-CEM cell lines.